2014
DOI: 10.1002/jib.160
|View full text |Cite
|
Sign up to set email alerts
|

Humulus lupulus- a story that begs to be told. A review

Abstract: The hop cones of the female plant of the common hop species Humulus lupulus L. are grown almost exclusively for the brewing industry. Only the cones of the female plants are able to secrete the fine yellow resinous powder (i.e. lupulin glands). It is in these lupulin glands that the main brewing principles of hops, the resins and essential oils, are synthesized and accumulated. Hops are of interest to the brewer since they impart the typical bitter taste and aroma to beer and are responsible for the perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
272
1
26

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(337 citation statements)
references
References 192 publications
(359 reference statements)
5
272
1
26
Order By: Relevance
“…Ferulate has been characterized in hop extracts ; however, analysis of the aqueous fraction of hop extracts in this study revealed no measurable ferulate (data not shown) at the micromolar detection limit of NMR. Myrcene is one of most abundant molecules found in hop oil and was the only hop aroma compound that was able to be identified in this work. Myrcene was recently reported to be present at 3 μM in beer , which is at the detection limit of our technique.…”
Section: Resultsmentioning
confidence: 93%
“…Ferulate has been characterized in hop extracts ; however, analysis of the aqueous fraction of hop extracts in this study revealed no measurable ferulate (data not shown) at the micromolar detection limit of NMR. Myrcene is one of most abundant molecules found in hop oil and was the only hop aroma compound that was able to be identified in this work. Myrcene was recently reported to be present at 3 μM in beer , which is at the detection limit of our technique.…”
Section: Resultsmentioning
confidence: 93%
“…Trpkost piv nepřímo úměrně korelovala pouze s rozdílem mezi zdánlivým a dosažitelným prokvašením (r = -0,417) a koncentrací původní mladiny (r = -0,498), vyšší koncentrace extraktu, nižší prokvašení pravděpodobně snižuje trpkou chuť. Trpkost chuti piva je přisuzována některým polyfenolovým látkám sladu (Narziss 1992(Narziss , 1995, chmele (Almaguer et al, 2014) a alkaloidům hordatinům, pocházejícím ze sladu (Kageyama et al, 2011).…”
Section: Brewing Trialsunclassified
“…Higher concentration of extract and lower attenuation probably reduce astringency. The astringency of beer is attributed to certain polyphenol substances from malt (Narziss 1992(Narziss , 1995, hops (Almaguer et al, 2014) and the alkaloids hordatins derived from malt (Kageyama et al, 2011).…”
Section: Brewing Trialsmentioning
confidence: 99%
“…The phenolic content of malted barley depends on the malting regime, with higher levels of malt modification resulting in a higher content of free phenolic acids . There is a myriad of antioxidant compounds derived from hops ( Humulus lupulus L.): Resinous compounds like α ‐acids or prenylated chalcones and non‐resin phenolic compounds like phenolic acids or flavonoids . Hop is either added at the beginning of wort boiling to achieve the desired bitterness or at the end of boiling or during whirlpool rest to impart a hoppy aroma to the final beer .…”
Section: Introductionmentioning
confidence: 99%